Learning During COVID19 University Closure: Case Studies of University of India - Dr. Mahesh Sarva et al. (Al-Qanṭara, 2022)
Abstract The aim of this present study was to explore the experiences of under graduate and post-graduate level students who abruptly transitioned from classroom learning to an online learning environment due to the COVID-19 pandemic. The research question was: What strengths and challenges are associated with online learning among under graduate and post-graduate students abruptly transitioning from a classroom to an online learning environment due to the COVID-19 pandemic? Participants were 30 undergraduate English students at Poland university, College of Education for Human Sciences and 20 undergraduate students at Al-Muthanna University. All participants completed a 10-item questionnaire. Data were analyzed using a six-step thematic approach and was interpreted through the lens of the Community of Inquiry theoretical framework. Findings indicated that online courses strengths included increased student engagement and flexibility, prior familiarity with teaching, increased personal time, and the use of multiple learning modalities. Challenges included problems with teaching, reduced engagement due to family interruptions, and lack of visual cues. Limitation of this study was the small sample size, which may limit the ability to generalize the findings to other students. These findings provide insight into the issues which can hinder success in online programs.